Reproductive emergencies in the bitch: a retrospective study - MARTINS-BESSA, A.; CARDOSO, L.; COSTA, T.; MOTA, R.; ROCHA, A.; MONTENEGRO, L. (Journal of the Hellenic Veterinary Medical Society, 2018)
This study aimed at analyzing reproductive emergencies (RE) in bitches brought in to a general veterinary hospital during a 24 month-period; evaluating their clinical-epidemiological features; and assessing the results of applied therapy. RE accounted for 11.8% of all female dog emergency clinical cases. Pyometra and dystocia accounted for 56.0% and 32% of the RE, with three (Newfoundland, Siberian Husky, Chow-Chow) and nine breeds (Boston Terrier, French Bulldog, Bernese Mountain Dog, Yorkshire Terrier, St. Bernard, Maltese, Chihuahua, Doberman and Boxer) found at higher risk of pyometra and dystocia, respectively. Fifty-four (96.4%) cases of pyometra were surgically managed, with a mortality of 13.0%. Primary uterine inertia (19 cases) was the main cause (59.4%) of dystocia. Medical treatment was attempted in 23 cases of dystocia (71.9%) but found to be effective in only two of them, leading to a high percentage of caesarian sections (30/32 cases, 93.8%). Both pyometra and dystocia had a high percentage of success following surgery. The use of standardized diagnostic and treatment protocols for the approach of RE allowed favorable outcomes.